Ferritic stainless steel material, method for producing the same, and antibacterial and antiviral member
By depositing a large number of Cu-enriched phases on the grain interface of the ferritic stainless steel material and controlling the grain size and distribution, the problem of volatile antibacterial and antiviral properties of existing materials is solved, and long-term stable antibacterial and antiviral effects are achieved.
Patent Information
- Application Number
- JP2023181327
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-05-02
AI Technical Summary
The existing ferritic stainless steel materials have problems of uneven distribution and volatile dissipation in maintaining antibacterial and antiviral properties, especially in the use environment, which is difficult to maintain for a long time and stably.
The size and quantity of ε-Cu phases are ensured to reach the desired level by depositing a large amount of Cu-enriched phase (ε-Cu phase) on the grain interface and controlling the grain size and distribution of ε-Cu phases through hot and cold rolling processes.
The ferritic stainless steel material is realized to maintain antibacterial and antiviral properties in a long period of time, improving its application reliability in different usage environments.
Smart Images

Figure 2025070784000005 
Figure 2025070784000001 
Figure 2025070784000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a ferritic stainless steel material, a manufacturing method thereof, and an antibacterial and antiviral member. [Background technology]
[0002] Stainless steel materials have excellent corrosion resistance and are therefore used in a wide range of applications, such as kitchen equipment, home appliances, medical equipment, interior building materials, and transport equipment, and are often used in environments where bacterial proliferation and viral adhesion are likely to occur. In recent years, there has been a growing concern about the adverse effects on the human body caused by such bacterial proliferation and viral adhesion, and in particular, antibacterial and antiviral properties are required not only for medical equipment and kitchen equipment, where cleanliness is essential, but also for various components used in buildings and transport equipment where many people gather.
[0003] Metal elements such as Ag and Cu are known to have antibacterial and antiviral properties, and so stainless steel materials and manufacturing methods for them that have been imparted with antibacterial and antiviral properties by adding these metal elements have been proposed. For example, Patent Document 1 proposes a ferritic stainless steel material with excellent antibacterial properties, which contains 0.1 wt % or less C, 2 wt % or less Si, 2 wt % or less Mn, 10 to 30 wt % Cr, 0.4 to 3 wt % Cu, with the balance being substantially Fe, and in which a Cu-rich phase (ε-Cu phase) precipitated by aging treatment is dispersed in the matrix at a rate of 0.2 vol % or more. Patent Document 2 proposes a method for manufacturing a ferritic stainless steel material with excellent antibacterial properties, in which a ferritic stainless steel containing 0.1 wt% or less C, 2 wt% or less Si, 2 wt% or less Mn, 10 to 30 wt% Cr, 0.4 to 3 wt% Cu, with the balance being substantially Fe, is hot-rolled, and then cooled in the temperature range of 900°C to 500°C at a rate of 10°C / min or less to precipitate 0.2 vol% or more of a Cu-rich phase (ε-Cu phase).
[0004] Patent Document 3 proposes a stainless steel sheet with low contact resistance, which has a substrate of austenitic or ferritic stainless steel containing 1.0 wt % or more of Cu and in which a Cu-rich phase (ε-Cu phase) is dispersed and precipitated in a matrix at a rate of 0.2 vol % or more, and in which a passive film is formed on the surface of the substrate excluding the precipitation portions of the Cu-rich phase. Patent Document 4 describes a steel sheet containing, by mass%, 0.04% or less C, 0.04% or less N, 0.28% or less Si, 0.3% or less Mn, 0.03% or less P, 0.002% or less S, 14 to 22% Cr, more than 1% but not more than 5% Cu, and 0.1% or more but not more than 5% Ni, which satisfies the condition Cu(%) ≧ Ni(%) ≧ 0.1 × Cu(%), and which contains 0 to 2.5% Mo and 0 to 0.5% Nb. A ferritic stainless steel material with excellent antibacterial properties has been proposed, which has a Cu-enriched layer (ε-Cu phase) containing 6 mass% or more of Cu on the surface of a ferritic stainless steel containing 8% Mn, 0-0.2% Ti, 0-0.03% Ca, 0-0.03% Ce, 0-0.03% La, 0-0.03% Y, 0-0.03% REM, and the balance being Fe and unavoidable impurities.
[0005] Patent Document 5 proposes a ferritic stainless steel material for kitchen appliances, which contains, by mass%, C: 0.001-0.050%, Si: 0.01-1.0%, Mn: 0.01-2.0%, P: 0.05% or less, S: 0.01% or less, Al: 0.001-1.0%, Cr: 11.0-32.0%, Cu: 0.4-4.0%, N: 0.001-0.050%, one or two of Ti: 0.10-0.60%, Nb: 0.10-0.60%, the balance being Fe and unavoidable impurities, and further contains 0.10-2.97 volume% of ε-Cu phase, and the average grain size of the ε-Cu phase is 30 nm or less.
[0006] However, the ferritic stainless steel materials disclosed in the above patent documents do not have a suitable distribution of the ε-Cu phase, so that the desired antibacterial properties may not be obtained or the antibacterial properties may be easily lost early. In addition, since viruses are smaller than bacteria, when viruses are attached between the ε-Cu phases, the antiviral properties may be hardly obtained. Therefore, in Patent Document 6, the applicant proposed a ferritic stainless steel material in which the distribution state of the ε-Cu phase (particularly, the area ratio of the ε-Cu phase on the surface, the average particle size of the ε-Cu phase, and the maximum interparticle distance of the ε-Cu phase) was controlled in addition to the composition. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 3223418 Publication [Patent Document 2] Patent No. 3498770 [Patent Document 3] Patent No. 4368985 [Patent Document 4] Patent No. 4038832 [Patent Document 5] Patent No. 6519023 [Patent Document 6] JP 2022-151128 A Summary of the Invention [Problem to be solved by the invention]
[0008] The ferritic stainless steel material described in Patent Document 6 has a controlled distribution state of the ε-Cu phase, and therefore can maintain better antibacterial and antiviral properties for a long period of time than the ferritic stainless steel materials described in Patent Documents 1 to 5. However, the ferritic stainless steel material described in Patent Document 6 may have a small ε-Cu phase or a small amount of the phase, so that depending on the usage environment, the durability of the antibacterial and antiviral properties may still be insufficient.
[0009] The present invention aims to provide a ferritic stainless steel material capable of stably maintaining antibacterial and antiviral properties for a long period of time, a method for producing the same, and an antibacterial and antiviral component. [Means for solving the problem]
[0010] In order to solve the above problems, the present inventors conducted extensive research into ferritic stainless steel materials. As a result, based on the knowledge that the ε-Cu phase is likely to precipitate at grain boundaries and that the ε-Cu phase precipitated at grain boundaries is larger than the ε-Cu phase precipitated within grains, they discovered that by making the crystal grains finer and increasing the crystal grain boundaries, and precipitating a coarse ε-Cu phase at the crystal grain boundaries, the effect of maintaining antibacterial and antiviral properties can be improved, which led to the completion of the present invention.
[0011] That is, the present invention provides a steel having an ε-Cu phase at the grain boundaries, There are 100 or more ε-Cu phases each having a major axis of 40 nm or more in a 50 μm square cross-sectional area, and The present invention relates to a ferritic stainless steel material having an average crystal grain size of 30 μm or less.
[0012] The present invention also provides a method for producing the ferritic stainless steel material, comprising the steps of: A hot rolling process in which the ferritic stainless steel slab is hot rolled at a finishing hot rolling temperature of 800°C to 1050°C at a finishing rolling reduction rate of 50.0% or more to obtain a hot rolled material; A cooling step of cooling the hot-rolled material obtained in the hot rolling step to a temperature of 500°C or less at an average cooling rate of 10.0°C / sec or more; an annealing process in which the hot-rolled material cooled in the cooling process is annealed at a temperature of 750 to 900°C; The present invention relates to a manufacturing method comprising the steps of:
[0013] Furthermore, the present invention relates to an antibacterial and antiviral member containing the ferritic stainless steel material. Effect of the Invention
[0014] According to the present invention, it is possible to provide a ferritic stainless steel material capable of stably maintaining antibacterial and antiviral properties for a long period of time, a method for producing the same, and an antibacterial and antiviral member. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is an enlarged schematic view of a cross section of a typical ferritic stainless steel material of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention. In this specification, the "%" designation for components means "% by mass" unless otherwise specified.
[0017] The ferritic stainless steel material according to the embodiment of the present invention has an ε-Cu phase (also called a "Cu-enriched phase") at the grain boundaries. Here, in this specification, the term "stainless steel material" refers to a material formed from stainless steel, and the shape of the material is not particularly limited. Examples of the shape of the material include a plate shape (including a strip shape), a rod shape, a tube shape, and the like. In addition, the material may be various shaped steels having a cross-sectional shape such as a T shape or an I shape. In addition, in this specification, "ferritic" means that the metal structure is mainly ferritic phase at room temperature. Therefore, "ferritic" also includes those that contain small amounts of phases other than ferritic phase (e.g., austenite phase, martensite phase, etc.). However, "ferritic" does not include a multi-phase structure of ferritic phase and austenite phase, a multi-phase structure of ferritic phase and martensite phase, or a multi-phase structure of ferritic phase, austenite phase, and martensite phase.
[0018] FIG. 1 is an enlarged schematic diagram of a cross section of a typical ferritic stainless steel material of the present invention. As shown in FIG. 1, a ferritic stainless steel material 10 includes crystal grains 20 and an ε-Cu phase 40 precipitated at grain boundaries 30 between the crystal grains 20 .
[0019] In the ferritic stainless steel material 10, the average grain size of the crystal grains 20 is 30 μm or less. Since the ε-Cu phase 40 is likely to precipitate at the grain boundaries 30 between the crystal grains 20, the size and amount of the ε-Cu phase 40 precipitated at the grain boundaries 30 can be increased by controlling the average grain size of the crystal grains 20 to 30 μm or less. From the viewpoint of enhancing this effect, the average grain size of the crystal grains 20 is preferably 25 μm or less, more preferably 20 μm or less, and further preferably 15 μm or less. The lower limit of the average grain size of the crystal grains 20 is not particularly limited because the smaller the better, but is typically 1 μm, preferably 2 μm, and more preferably 3 μm.
[0020] Here, the average crystal grain size of the crystal grains 20 means the average value of the crystal grain size (circle equivalent diameter) of the crystal grains 20 surrounded by the crystal grain boundaries 30 having a crystal orientation difference of 2° or more. The average grain size of the crystal grains 20 is obtained by analyzing the cross section of the ferritic stainless steel material 10 by EBSD (Electron Back Scattering Diffraction). Specifically, the average grain size of the crystal grains 20 is obtained as follows. First, a 15 mm square sample of the ferritic stainless steel material 10 is cut out by cutting or the like, and the L-section (a section parallel to the rolling direction and perpendicular to the rolling surface) is mechanically polished to a mirror surface, and then electrolytically polished. For the L-section thus processed, EBSD analysis is performed at 0.2 μm step intervals in an 80 μm square area in a field of view of 1000 times magnification, and crystal grain boundaries 30 with a crystal orientation difference of 2° or more are identified. The area of each crystal grain 20 surrounded by this crystal grain boundary 30 is then defined as S [μm 2 ], the diameter of a circle having the same area as the crystal grain 20 is defined as D [μm], and the crystal grain size (average crystal grain size per field of view) [μm] is calculated by the following formula (1). This operation is performed for five fields of view to determine the crystal grain size for each field, and the average of these is defined as the average crystal grain size.
[0021]
number
[0022] In the ferritic stainless steel material 10, there are 100 or more ε-Cu phases 40 with a major axis of 40 nm or more in a 50 μm square cross-sectional area. If the major axis of the ε-Cu phases 40 is 40 nm or more, the size of the ε-Cu phases 40 can be said to be large. Also, if there are 100 or more ε-Cu phases 40 of this size in a 50 μm square cross-sectional area, the amount of ε-Cu phases 40 can be said to be large. Therefore, by having such characteristics, it can be said that the coarse ε-Cu phases 40 are also exposed on the surface, and therefore the antibacterial and antiviral properties can be stably maintained for a long period of time.
[0023] Here, the number of ε-Cu phases 40 with a major axis of 40 nm or more present in a 50 μm square cross-sectional area is obtained by observing the surface of the ferritic stainless steel material 10 with a SEM (scanning electron microscope). Specifically, the number of ε-Cu phases 40 with a major axis of 40 nm or more present in a 50 μm square cross-sectional area is obtained as follows. First, a 15 mm square sample of the ferritic stainless steel material 10 is cut out by cutting or the like, and the L cross section (a cross section parallel to the rolling direction and perpendicular to the rolling surface) is buffed to a mirror surface, and then finished by colloidal polishing to remove surface distortion. A 50 μm square region of the L cross section thus treated is observed with an SEM. In the backscattered electron image of the SEM, the ε-Cu phases 40 are identified from the difference in contrast, and the number of ε-Cu phases 40 with a major axis of 40 nm or more is measured. This operation is performed in 10 fields of view to determine the number of ε-Cu phases 40 with a major axis of 40 nm or more, and their average value is calculated. The long diameter of the ε-Cu phase 40 means the diameter of the longest part in a backscattered electron image of an SEM.
[0024] The ferritic stainless steel material 10 having the above-mentioned characteristics is considered to have a structure similar to that shown in FIG. 1 on the surface. However, a passive film is formed on the surface where the ε-Cu phase 40 is not exposed. Since the ε-Cu phase 40 is exposed on the surface, when moisture comes into contact with the surface of the ferritic stainless steel material 10, Cu ions can be eluted from the ε-Cu phase 40. For example, when a person's hand touches the surface of the ferritic stainless steel material 10, Cu ions can be eluted from the ε-Cu phase 40 by the moisture on the hand. Therefore, even if bacteria adhere to the surface, they can be sterilized, and even if viruses adhere to the surface, they can be inactivated and eventually killed. In addition, since a passive film is formed on the surface where the ε-Cu phase 40 is not exposed, the corrosion resistance is also good.
[0025] The composition of the ferritic stainless steel material 10 is not particularly limited, but preferably contains Cr: 13.00 to 32.00%, Cu: 0.50 to 4.00%. More preferably, the ferritic stainless steel material 10 further contains C: 0.100% or less, Si: 1.00% or less, Mn: 3.00% or less, Ni: 4.00% or less, P: 0.050% or less, S: 0.030% or less, N: 0.100% or less, the total of at least one of Ti and Nb: 6(C+N) to 1.00%, Sn: 0.020% or less, with the balance being Fe and impurities. Furthermore, the ferritic stainless steel material 10 may, if necessary, further contain one or more selected from Mo: 3.00% or less, Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, and B: 0.0100% or less.
[0026] In this specification, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and in the manufacturing process when industrially manufacturing the ferritic stainless steel material 10, and are acceptable within a range that does not adversely affect the present invention. For example, the impurities include unavoidable impurities. Regarding the content of each element, "xx% or less" includes amounts that are xx% or less but exceed 0% (especially exceeding the impurity level). Hereinafter, each component will be described in detail.
[0027] <Cr: 13.00 - 32.00%> Cr is an important element for maintaining the corrosion resistance and oxidation resistance of the ferritic stainless steel material 10. However, if the Cr content is too high, it will lead to an increase in refining costs, hardening due to solid solution strengthening (decrease in toughness), and a decrease in the workability of the ferritic stainless steel material 10. Therefore, the upper limit value of the Cr content is controlled at 32.00%, preferably 31.50%, more preferably 31.00%, and still more preferably 30.50%. On the other hand, if the Cr content is too low, sufficient corrosion resistance cannot be obtained. Therefore, the lower limit value of the Cr content is controlled at 13.00%, preferably 14.00%, more preferably 15.00%, and still more preferably 16.00%.
[0028] <Cu: 0.50 - 4.00%> Cu is an element necessary for precipitating the ε-Cu phase 40 that provides antibacterial and antiviral properties. To obtain this effect, the lower limit value of the Cu content is controlled at 0.50%, preferably 0.80%, more preferably 1.00%, and still more preferably 1.30%. On the other hand, if the Cu content is too high, the ferrite phase becomes unstable and the manufacturing cost also increases. Therefore, the upper limit value of the Cu content is controlled at 4.00%, preferably 3.50%, more preferably 3.00%, and still more preferably 2.50%.
[0029] <C: 0.100% or less> C is an element that improves the strength of the ferritic stainless steel material 10. However, if the content of C is too high, in addition to becoming hard and the workability decreasing, sensitization occurs when it is affected by the heat of welding or the like, and the corrosion resistance of the ferritic stainless steel material 10 decreases. Therefore, the upper limit value of the content of C is controlled to 0.100%, preferably 0.060%, more preferably 0.040%, and still more preferably 0.030%. On the other hand, the lower limit value of the content of C is not particularly limited, but from the viewpoint of suppressing the refining cost, it is preferably 0.001%, more preferably 0.003%, and still more preferably 0.005%.
[0030] <Si: 1.00% or less> Si is an element that generates a ferrite phase (α phase) and is an element effective for improving the corrosion resistance of the ferritic stainless steel material 10. However, if the content of Si is too high, it becomes hardened and the workability of the ferritic stainless steel material 10 decreases. Also, when welding is performed, the toughness of the welded part decreases. Therefore, the upper limit value of the content of Si is controlled to 1.00%, preferably 0.80%, more preferably 0.70%, and still more preferably 0.50%. On the other hand, the lower limit value of the content of Si is not particularly limited, but it is preferably 0.01%, more preferably 0.05%, and still more preferably 0.10%.
[0031] <Mn: 3.00% or less> Mn is an element that improves the heat resistance of the ferritic stainless steel material 10. However, if the content of Mn is too high, MnS, which becomes a corrosion initiation point, is likely to be generated, and the ferrite phase becomes unstable. Therefore, the upper limit value of the content of Mn is controlled to 3.00%, preferably 2.00%, more preferably 1.50%, and still more preferably 1.00%. On the other hand, the lower limit value of the content of Mn is not particularly limited, but it is preferably 0.01%, more preferably 0.05%, and still more preferably 0.10%.
[0032] <Ni: 4.00% or less> Ni is an element that improves the corrosion resistance (especially intergranular corrosion resistance) of the ferritic stainless steel material 10. However, if the Ni content is too high, the ferrite phase becomes unstable similar to Mn, and the manufacturing cost also increases. Therefore, the upper limit value of the Ni content is controlled to 4.00%, preferably 3.00%, more preferably 2.00%, and still more preferably 1.00%. On the other hand, the lower limit value of the Ni content is not particularly limited, but is preferably 0.01%, more preferably 0.02%, and still more preferably 0.03%.
[0033] <P: 0.050% or less> Since the ferritic stainless steel material 10 has a high Cu content, if the P content is high, it is easy to form a Cu and low-melting-point intermetallic compound. This intermetallic compound causes cracks and the like during hot rolling, so it is desirable to reduce the P content. Also, if the P content is high, it also causes a decrease in weldability and workability. Therefore, the upper limit value of the P content is controlled to 0.050%, preferably 0.040%, and more preferably 0.030%. On the other hand, the lower limit value of the P content is not particularly limited, but since refining costs are incurred for reduction, it is preferably 0.001%, more preferably 0.005%, and still more preferably 0.010%.
[0034] <S: 0.030% or less> Similar to P, if the S content is high, it is easy to form a Cu and low-melting-point intermetallic compound, which causes cracks and the like during hot rolling. Also, if the S content is high, MnS, which is a corrosion initiation point, is likely to be generated, and the toughness of the welded part decreases when welding is performed. Therefore, the upper limit value of the S content is controlled to 0.030%, preferably 0.020%, and more preferably 0.010%. On the other hand, the lower limit value of the S content is not particularly limited, but since refining costs are incurred for reduction, it is preferably 0.0001%, more preferably 0.0002%, and still more preferably 0.0003%.
[0035] <N: 0.100% or less> N is an element effective in improving the corrosion resistance of the ferritic stainless steel material 10. However, if the content of N is too high, in addition to becoming hard and reducing workability, sensitization occurs when it is affected by heat such as welding, and the corrosion resistance of the ferritic stainless steel material 10 decreases. Therefore, the upper limit value of the content of N is controlled to 0.100%, preferably 0.080%, more preferably 0.050%, and still more preferably 0.030%. On the other hand, the lower limit value of the content of N is not particularly limited, but from the viewpoint of suppressing refining costs, it is preferably 0.001%, more preferably 0.003%, and still more preferably 0.005%.
[0036] <Total of at least one of Ti and Nb: 6(C + N) to 1.00%> Nb and Ti are elements that affect the intergranular corrosion resistance (sensitization suppression effect) of the ferritic stainless steel material 10. Also, Nb and Ti are elements effective in immobilizing C and N. Therefore, the total content of Nb and Ti is determined based on the amounts of C and N. That is, the lower limit value of the total content of Nb and Ti is 6(C + N)% from the viewpoint of obtaining the above effects. However, if the total content of Nb and Ti is too high, in addition to an increase in manufacturing costs, the workability and surface quality of the ferritic stainless steel material 10 decrease. Therefore, the upper limit value of the total content of Nb and Ti is 1.00%, preferably 0.80%, and more preferably 0.60%. Also, the individual contents of Nb and Ti are each preferably 0.05% or more, more preferably 0.06% or more, from the viewpoint of suppressing the coarsening of the crystal grains 20 during annealing. In particular, Nb can effectively suppress the coarsening of the crystal grains 20 by the pinning effect of carbides and nitrides such as NbC and NbN because it forms carbides and nitrides such as NbC and NbN.
[0037] <Sn: 0.020% or less> Sn is an element effective in improving the oxidation resistance of the ferritic stainless steel material 10. However, if the content of Sn is too high, it will cause segregation and become a factor in reducing the manufacturability. Therefore, the upper limit value of the Sn content is controlled to be 0.020%, preferably 0.015%, more preferably 0.010%. On the other hand, the lower limit value of the Sn content is not particularly limited, but from the viewpoint of obtaining the effect of Sn, it is preferably 0.001%, more preferably 0.002%.
[0038] <Mo: 3.00% or less> Mo is an element effective in improving the corrosion resistance and oxidation resistance of the ferritic stainless steel material 10. However, if the content of Mo is too high, it will lead to a decrease in workability and an increase in manufacturing cost. Therefore, the upper limit value of the Mo content is controlled to be 3.00%, preferably 2.50%, more preferably 2.00%. On the other hand, the lower limit value of the Mo content is not particularly limited, but from the viewpoint of obtaining the effect of Mo, it is preferably 0.01%, more preferably 0.03%, still more preferably 0.05%.
[0039] <Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less> Al, Zr, Co, V, and W are elements effective in improving the oxidation resistance of the ferritic stainless steel material 10. However, if the content of these elements is too high, it will lead to a decrease in workability and toughness and an increase in manufacturing cost. Therefore, the upper limit value of the content of these elements is controlled to be 1.00% for all, preferably 0.80%, more preferably 0.60%. On the other hand, the lower limit value of the content of these elements is not particularly limited for all, but from the viewpoint of obtaining the effect of these elements, it is preferably 0.01%, more preferably 0.03%, still more preferably 0.05%.
[0040] <REM: 0.100% or less, Ca: 0.100% or less> REM (rare earth elements) and Ca are elements effective in improving the oxidation resistance of the ferritic stainless steel material 10. However, if the contents of these elements are too high, it will lead to an increase in manufacturing costs. Therefore, the upper limit values of the contents of these elements are all controlled to 0.100%, preferably 0.080%, more preferably 0.050%. On the other hand, the lower limit values of the contents of these elements are not particularly limited, but from the viewpoint of obtaining the effects of these elements, they are preferably 0.001%, more preferably 0.003%, and still more preferably 0.005%. Note that REM refers to the general term for two elements, scandium (Sc) and yttrium (Y), and 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu). These may be used alone or as a mixture.
[0041] <B: 0.0100% or less> B is an element effective in improving the secondary workability of the ferritic stainless steel material 10. However, if the content of B is too high, it will cause a decrease in fatigue strength. Therefore, the upper limit value of the content of B is controlled to 0.0100%, preferably 0.0070%. On the other hand, the lower limit value of the content of B is not particularly limited, but from the viewpoint of obtaining the effects of B, it is preferably 0.0001%, more preferably 0.0003%.
[0042] The type of the ferritic stainless steel material 10 according to the embodiment of the present invention is not particularly limited, but it is preferably a hot-rolled (hot-rolled and annealed) material or a cold-rolled (cold-rolled and annealed) material. In the case of a hot-rolled (hot-rolled and annealed) material, its thickness is generally 3 mm or more. In the case of a cold-rolled (cold-rolled and annealed) material, its thickness is generally less than 3 mm.
[0043] The manufacturing method of the ferritic stainless steel material 10 according to the embodiment of the present invention is not particularly limited as long as it can manufacture the ferritic stainless steel material 10 having the above characteristics. Hereinafter, a typical manufacturing method of the ferritic stainless steel material 10 according to the embodiment of the present invention will be described.
[0044] The method for producing the ferritic stainless steel material 10 according to the embodiment of the present invention includes a hot rolling step, a cooling step, and an annealing (heat treatment) step. The hot rolling process is a process in which a ferritic stainless steel slab is hot rolled to obtain a hot rolled material. Specifically, the ferritic stainless steel slab is roughly rolled, and then finish hot rolled (finish rolling) to obtain a hot rolled material. This hot rolled material may be wound into a coil. The ferritic stainless steel slab is not particularly limited, but can be obtained, for example, by melting stainless steel having the above composition and forging or casting it.
[0045] Rough rolling is performed at a higher temperature than finish hot rolling, and therefore has little effect on the strain applied to the hot-rolled material. Therefore, the conditions of rough rolling are not particularly limited and may be appropriately set according to the composition of the ferritic stainless steel slab. On the other hand, the conditions of finish hot rolling affect the strain that acts as a driving force for recrystallization, so the rolling ratio and temperature of finish hot rolling are controlled from the viewpoint of applying sufficient strain to the hot-rolled material. The rolling ratio of the finish hot rolling (hereinafter referred to as "finish rolling ratio") is 50.0% or more. By controlling the finish rolling ratio within this range, sufficient strain acting as a driving force for recrystallization is applied, making it possible to refine the crystal grains 20. From the viewpoint of stably securing this effect, the finish rolling ratio is preferably 51.0% or more, more preferably 52.0% or more. On the other hand, if the finish rolling ratio is less than 50.0%, the crystal grains 20 become coarse, and the amount of ε-Cu phase 40 precipitated at the crystal grain boundaries 30 between the crystal grains 20 decreases. The upper limit of the finish rolling ratio is not particularly limited, but is preferably 98.0%, more preferably 95.0%.
[0046] The temperature of the finish hot rolling (hereinafter referred to as "finish hot rolling temperature") is 800 to 1050°C. By controlling the finish hot rolling temperature within this range, the coarsening of the crystal grains 20 is suppressed, while the precipitation of the ε-Cu phase 40 is suppressed as much as possible from the end of the finish hot rolling to the cooling process. As a result, the ε-Cu phase 40 of the crystal grain boundaries 30 grows in the annealing process, so that the size and amount of the ε-Cu phase 40 can be increased. If the finish hot rolling temperature is less than 800°C, recrystallization is not completed to a certain extent at the end of the finish hot rolling. As a result, the ε-Cu phase 40 precipitates not only in the crystal grain boundaries 30 but also in the crystal grains 20 in the annealing process, so that the size and amount of the ε-Cu phase 40 of the crystal grain boundaries 30 become insufficient. The upper limit of the finish hot rolling temperature is preferably 950°C, more preferably 930°C, and even more preferably 900°C, from the viewpoint of stably securing the above-mentioned effects.
[0047] The cooling step is performed by cooling the hot-rolled material obtained in the hot rolling step to a temperature of 500°C or less at an average cooling rate of 10.0°C / sec or more. Rapid cooling under such conditions can suppress the precipitation of the ε-Cu phase 40 in the crystal grains 20 in the precipitation temperature range of the ε-Cu phase 40 (900 to 500°C) while suppressing the coarsening of the crystal grains 20. On the other hand, if the average cooling rate is less than 10.0°C / sec, the crystal grains 20 will become coarse. The cooling method in the cooling step is not particularly limited, and any method known in the technical field (such as air cooling or water cooling) can be used.
[0048] The average grain size of the hot-rolled material after the cooling step is preferably 25 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less. With such an average grain size, it can be said that the coarsening of the grains 20 is sufficiently suppressed in the hot-rolling step and the cooling step. The lower limit of the average grain size is not particularly limited because the smaller the better, but is typically 1 μm, preferably 3 μm, and more preferably 5 μm. Here, the average crystal grain size of the hot-rolled material is determined by analyzing the cross section of the hot-rolled material with EBSD, similar to the method for measuring the average crystal grain size of the ferritic stainless steel material 10 described above. Specifically, a 15 mm square sample of the hot-rolled material is cut out by cutting or the like, and the L-section (a section parallel to the rolling direction and perpendicular to the rolling surface) is mechanically polished to a mirror surface, and then electrolytically polished. For the L-section thus processed, EBSD analysis is performed at 0.2 μm step intervals in an 80 μm square area in a field of view of 1000 times magnification, and crystal grain boundaries 30 with a crystal orientation difference of 2° or more are identified. The area of each crystal grain 20 surrounded by this crystal grain boundary 30 is then defined as S [μm 2 ], the diameter of a circle having the same area as the crystal grain 20 is defined as D [μm], and the crystal grain size (average crystal grain size per field of view) [μm] is calculated by the above formula (1). This operation is performed for five fields of view to determine the crystal grain size for each field, and the average of these is defined as the average crystal grain size.
[0049] The annealing step is performed by annealing the hot-rolled material cooled in the cooling step at 750 to 900°C. This annealing step allows the fine "seeds" of the ε-Cu phase 40 precipitated in the cooling step to grow. If the annealing temperature is less than 750°C, the fine "seeds" of the ε-Cu phase 40 do not grow sufficiently, and the size of the ε-Cu phase 40 becomes small. If the annealing temperature exceeds 900°C, the ε-Cu phase 40 dissolves in the matrix, and the amount of the ε-Cu phase 40 decreases. The annealing time is not particularly limited and may be appropriately adjusted depending on the annealing temperature, but is preferably 4 hours or more, more preferably 4 to 20 hours, and further preferably 5 to 10 hours.
[0050] After the annealing step, a surface layer removing step may be further performed as necessary, which involves pickling, polishing, etc. By performing the surface layer removing step, scale formed on the surface, a Cr-depleted layer, etc. can be removed. The thickness of the surface layer removed in the surface layer removing step is not particularly limited and may be appropriately adjusted depending on the composition of the ferritic stainless steel slab, etc. For example, when removing a Cr-depleted layer, it is preferable to remove a surface layer having a thickness of 10 μm or more.
[0051] When the ferritic stainless steel material 10 is a cold-rolled material, the method may further include a cold rolling step and a finish annealing step after the heat treatment step. When the surface layer removing step is performed after the heat treatment step, the cold rolling step and the finish annealing step may be performed after the surface layer removing step, or the cold rolling step and the finish annealing step may be performed before the surface layer removing step. Also, the surface layer removing step may be performed last after the cold rolling step and the finish annealing step.
[0052] The cold rolling process is a process in which the annealed material obtained in the annealing process is cold rolled to obtain a cold rolled material. The conditions of the cold rolling are not particularly limited and can be appropriately adjusted depending on the type of cold rolled material required.
[0053] The final annealing process is a process in which the cold-rolled material obtained in the cold rolling process is final annealed at a temperature of 1100° C. or less. By setting the temperature of the final annealing to 1100° C. or less, it is possible to suppress the ε-Cu phase 40 precipitated at the grain boundaries 30 from dissolving in the matrix. If the temperature of the final annealing exceeds 1100° C., the ε-Cu phase 40 will dissolve in the matrix, resulting in a decrease in the amount and size of the ε-Cu phase 40 precipitated at the grain boundaries 30. The final annealing time is not particularly limited and may be appropriately adjusted depending on the final annealing temperature, but is preferably within 300 seconds, more preferably 10 to 200 seconds.
[0054] The ferritic stainless steel material 10 according to the embodiment of the present invention can stably maintain antibacterial and antiviral properties for a long period of time, and therefore can be used as an antibacterial and antiviral component.
[0055] The antibacterial and antiviral member according to the embodiment of the present invention includes the above-mentioned ferritic stainless steel material 10. The above-mentioned ferritic stainless steel material 10 used in this antibacterial and antiviral member may be processed into various shapes by methods known in the technical field. The antibacterial and antiviral member according to the embodiment of the present invention may further include members other than the ferritic stainless steel material 10 described above. Examples of antibacterial and antiviral materials include, but are not limited to, various materials that are used in kitchen equipment, home appliances, medical equipment, interior building materials for buildings, transportation equipment, laboratory equipment, sanitary equipment, etc., and that require antibacterial and antiviral properties. EXAMPLES
[0056] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these.
[0057] Ferritic stainless steels having the compositions of steel types A to I shown in Table 1 (the balance being Fe and impurities) were melted and forged to form ferritic stainless steel slabs, which were then hot rolled to a thickness of 3 mm to obtain hot-rolled sheets, with the finish rolling reduction and finish hot rolling temperature controlled as shown in Table 2. The rolling reduction was controlled by changing the thickness of the ferritic stainless steel slab. The finish rolling reduction was determined as the sum of the rolling reductions at a temperature at which the material temperature was 1050°C or lower. The finish hot rolling temperature was controlled by adjusting the time from rough rolling to finish rolling. Next, the hot-rolled sheet was cooled to 500° C. at the average cooling rate shown in Table 2. The average cooling rate was controlled by adjusting the air-cooling and water-cooling conditions. Next, the cooled hot-rolled sheet was cut into a size of 300 mm (rolling direction) x 100 mm (width direction), placed in an EREMA electric furnace, and BAF annealed in air at the annealing temperature shown in Table 2 for 8 hours. Next, the obtained annealed sheet was descaled by dry honing and fluoronitric acid, and then dry polished using SiC abrasive paper. The dry polishing was finished with SiC abrasive paper of grain size #600. The ferritic stainless steel sheet obtained in this way is called "hot-rolled annealed sheet".
[0058] Some of the hot-rolled and annealed sheets were cold-rolled to a thickness of 1 mm to obtain cold-rolled sheets, which were then placed in an EREMA electric furnace and finish-annealed in an air atmosphere at the annealing temperatures shown in Table 2 for 30 seconds. Next, the obtained annealed sheet was descaled with fluoronitric acid, and then dry polished using SiC abrasive paper. The dry polishing was finished with SiC abrasive paper with a grain size of #600. The ferritic stainless steel sheet obtained in this way is called "cold-rolled annealed sheet."
[0059] [Table 1]
[0060] [Table 2]
[0061] The obtained ferritic stainless steel sheets (hot-rolled and annealed sheets or cold-rolled and annealed sheets) were subjected to the following evaluations.
[0062] (Average grain size of grains) The average grain size of the grains in the hot-rolled material and the ferritic stainless steel sheet (hot-rolled annealed sheet or cold-rolled annealed sheet) after the cooling process was determined by the above method. Note that the EBSD analysis was performed using JXA-8900 manufactured by JEOL Ltd.
[0063] (The number of ε-Cu phases with a major axis of 40 nm or more present in a 50 μm square cross-sectional area (hereinafter referred to as "the number of ε-Cu phases")) The number of ε-Cu phases was determined by the above method. A Schottky scanning electron microscope (SU5000, Hitachi High-Technologies Corporation) was used as the SEM.
[0064] (Cu elution test) In order to evaluate the sustainability of Cu elution from ferritic stainless steel sheets, the amount of Cu eluted was evaluated after immersing the ferritic stainless steel sheets in pure water for 10 hours. Specifically, the amount of Cu eluted was calculated as follows. First, a 33 mm square sample was cut out from a ferritic stainless steel sheet (hot-rolled annealed sheet or cold-rolled annealed sheet) by cutting or the like, and the entire surface of the sample was dry-polished with abrasive paper of grain size #600. Next, the sample was immersed in 1000 mL of pure water (room temperature) in a beaker, and the pure water was stirred by operating a magnet stirrer at a rotation speed of 1000 rpm, and this state was maintained for 10 hours. Next, after removing the sample from the pure water, the sample was immersed in 25 mL of 5% nitric acid aqueous solution (room temperature) for 2 hours, and the Cu concentration in the nitric acid aqueous solution after the test was measured by an ICP emission spectrometer (Shimadzu Corporation ICPE-9800). The obtained Cu concentration was divided by the surface area of the sample to obtain the Cu concentration per unit area (μg / cm 2 ) was calculated and this result was taken as the amount of Cu elution. In this evaluation, the amount of Cu elution was 0.03 μg / cm 2 If the above is true, it can be determined that the Cu elution is sustained satisfactorily and that the antibacterial and antiviral properties can be stably maintained for a long period of time.
[0065] (Corrosion resistance test) The corrosion resistance was evaluated by the following salt, dry and wet combined cycle test. First, a test piece of 100 mm (rolling direction) x 50 mm (width direction) was cut out from a ferritic stainless steel sheet (hot-rolled annealed sheet or cold-rolled annealed sheet), and three sides of the test piece (except one side in the width direction) were covered with resin (one-liquid condensation type RTV rubber KE44 manufactured by Shin-Etsu Chemical Co., Ltd.). Next, two polyethylene tubes of 20 mmφ x 10 mm were bonded onto a Bakelite plate of 70 mm x 150 mm, and the side of the test piece that was not covered with resin was placed on top of it and bonded. A salt-dry-wet combined cycle test (CCT) was performed on the measurement sample obtained in this way. The sample was placed in a CCT device so that the surface of the test piece for measurement was 75° to the horizontal plane and the side of the test piece for measurement that was not covered with resin was at the bottom, and five cycles were performed, each consisting of 5% salt spray (35°C, 2 hours), drying (60°C, 25% RH, 4 hours), and wetting (50°C, 95% RH, 2 hours). The measurement samples were then washed with water and dried, and the rust area ratio on the surface of the test pieces was evaluated (based on JIS G0595:2004). In this evaluation, a rating number (RN) of 6 or more (corresponding to a rust area ratio of 0.5% or less) was designated an A, and a rating number (RN) of less than 6 was designated a B. A rating number (RN) of 6 or more can be considered to have excellent corrosion resistance.
[0066] The results of the above evaluations are shown in Table 3.
[0067] [Table 3]
[0068] As shown in Table 3, the ferritic stainless steel sheets (hot-rolled annealed sheets or cold-rolled annealed sheets) of Examples 1 to 9 had average crystal grain sizes and the number of ε-Cu phases in appropriate ranges, and therefore had a large amount of Cu elution, and were confirmed to be capable of stably maintaining antibacterial and antiviral properties for a long period of time. In addition, the ferritic stainless steel sheets (hot-rolled annealed sheets or cold-rolled annealed sheets) of Examples 1 to 8 also had excellent corrosion resistance. In contrast, the ferritic stainless steel sheets (hot-rolled annealed sheets or cold-rolled annealed sheets) of Comparative Examples 1 to 7 had average grain sizes and / or the number of ε-Cu phases not within appropriate ranges, so the amount of Cu elution was small and the durability of antibacterial and antiviral properties was insufficient. Moreover, in Comparative Examples 8 and 9, the production of ferritic stainless steel sheets itself was not possible.
[0069] As can be seen from the above results, the present invention can provide a ferritic stainless steel material that can stably maintain antibacterial and antiviral properties for a long period of time, a method for producing the same, and an antibacterial and antiviral component. [Explanation of symbols]
[0070] 10 Ferritic stainless steel 20 Grains 30 Grain Boundaries 40 ε-Cu phase
Claims
1. It has an ε-Cu phase at the grain boundaries, There are 100 or more ε-Cu phases each having a major axis of 40 nm or more in a 50 μm square cross-sectional area, and A ferritic stainless steel material having an average crystal grain size of 30 μm or less.
2. The ferritic stainless steel material according to claim 1, comprising, on a mass basis, Cr: 13.00 to 32.00%, Cu: 0.50 to 4.00%.
3. The ferritic stainless steel material according to claim 2, further comprising, on a mass basis, C: 0.100% or less, Si: 1.00% or less, Mn: 3.00% or less, Ni: 4.00% or less, P: 0.050% or less, S: 0.030% or less, N: 0.100% or less, a total of at least one of Ti and Nb: 6(C+N) to 1.00%, Sn: 0.020% or less, and the balance consisting of Fe and impurities.
4. The ferritic stainless steel material according to claim 3, further comprising, on a mass basis, one or more selected from Mo: 3.00% or less, Al: 1.00% or less, Zr: 1.00% or less, Co: 1.00% or less, V: 1.00% or less, W: 1.00% or less, REM: 0.100% or less, Ca: 0.100% or less, and B: 0.0100% or less.
5. The ferritic stainless steel material according to any one of claims 1 to 4, which is used for an antibacterial and antiviral component.
6. A method for producing a ferritic stainless steel material according to any one of claims 1 to 4, A hot rolling process in which the ferritic stainless steel slab is hot rolled at a finishing hot rolling temperature of 800°C to 1050°C at a finishing rolling reduction rate of 50.0% or more to obtain a hot rolled material; A cooling step of cooling the hot-rolled material obtained in the hot rolling step to a temperature of 500° C. or less at an average cooling rate of 10.0° C. / sec or more; an annealing step of annealing the hot-rolled material cooled in the cooling step at a temperature of 750 to 900°C; A manufacturing method comprising:
7. The method according to claim 6, wherein the average grain size of the hot-rolled material after the cooling step is 25 μm or less.
8. A cold rolling process in which cold rolling is performed after the annealing process to obtain a cold rolled material; a finish annealing process in which the cold-rolled material obtained in the cold rolling process is finish-annealed at a temperature of 1100° C. or less; The method of claim 6 further comprising:
9. An antibacterial and antiviral member comprising the ferritic stainless steel material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Ferritic stainless steel, manufacturing method thereof, and antibacterial and antivirus member
JP2022151128A
Ferritic stainless steel with excellent antibacterial properties and method for manufacturing the same
JP3223418B2
Method for producing ferritic stainless steel with excellent antibacterial properties
JP3498770B2
Stainless steel material with excellent antibacterial properties and its manufacturing method
JP4038832B2
Stainless steel sheet with low contact resistance and method for manufacturing the same
JP4368985B2